A time for making sacrifices - Abd Razak, Dzulkifli (2008)
WITHIN the span of a week, almost the entire world has embraced the spirit of sacrifice, caring and forgiveness. Hari Raya Aidiladha, which was celebrated on Dec 20 by Muslims all over, is an unequivocal symbol in the Islamic tradition. The "Festival of the Sacrifice" commemorates Prophet's Ibrahim's (Abraham) willingness to sacrifice one of his sons, Ismail (Ishmael), as a sign of obedience to God's commandment. He was further encouraged by his son's acceptance of God's ultimate test of faith. As they remain steadfast, God in His Wisdom and Compassion spared Ismail such that Ibrahim's knife fell on a lamb instead, a substitute for his son. In many ways, it is also a mark of sanctity of human life among Muslims and for humankind.